(untitled) - Hermsen, Josee; Challacombe, Stephen (Lisse, The Netherlands, 2004)
This book presents information on all areas of equestrian sport as well as a guide to horse breeds and information on owning and caring for horses.
Includes index.
9-12
Keywords: Horses; Encyclopedias; Horsemanship; Encyclopedias